Estructura y utilización del follaje de las comunidades de pájaros en bosques templados del Valle de México - Nocedal, Jorge (Instituto de Ecología, A.C., 1984)
Températe forests are distributed over very extensivo areas in North America but in tropical Middle America are limited to montane zones, and at the present time these montane forests are threatened by man because of overpopulation. I studied the structure and use of foliage of bird communities in montane températe forests of , the Valley of México. In August and September of 1981 I censused bird communities in six températe forest study areas one each in oak woodland and pine-alder forest, and two each in pine forest and firforest using the variable circular-plot method. Overall bird densities were greater in broad-leaved forests than in coniferous forests. Species richness was similar between broad-leaved and pine forests but generally lower in fir forests. A similar trend was shown by bird species diversity (BSD). The oak woodland bird community was the most distinctive, whereas the pine-alder one was similar to the fir forests. Bird communities of the two pine forests had low similarity indices, whereas communities of fir forests had the highest índices. Qranivorous birds were very important in pine forests, whereas insectivores were the most important in broad-leaved and fir forests. Profiles of foliage stratification were used selectively by all the bird communities, and profiles of utiiization were significantly different between August and September for all the communities except that of the pine-alder forest. Among dietary categories and guilds, all but the seed-eaters used the profile of foliage stratification very selectively; this selectivity was especially marked for the salliers and the foliage gelaners. In a latitudinal gradient of températe forests over western North America and México, there were not big differences in species richness of bird communities from broad-leaved and mixed-conifer forests, but there was a decrease in the number of species from pine forests as latitude decreased. BSD decreased southwards in the broad-leaved forests and only slightly in mixed-conifer forests, whereas in pine forests BSD increased. Seed-eaters were relatively more abundant in the northem forests, whereas foliage gleaners were the most important in Southern forests, but not in the pine forests.